TINDAK PIDANA PERPAJAKAN DALAM PRESPEKTIF HUKUM PIDANA DAN HUKUM PAJAK - Hendharto Oetomo; Rizky Karo Karo (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
In some cases of tax-related criminal acts, the actions often involve offenses categorized as general crimes that conflict with the Criminal Law (KUHP). This study aims to analyze and examine the regulations concerning tax-related crimes in relation to the Criminal Law and to identify the obstacles encountered in prosecuting perpetrators of tax-related criminal acts in Indonesia. The research method used is a normative juridical approach, aimed at understanding, reviewing, and analyzing legal principles in a structured manner using normative textual instruments such as specific laws, the Criminal Code, and relevant literature. The results of this study indicate that tax-related criminal acts are not only associated with the provisions of the General Tax Provisions Law (UU KUP), but may also involve the Criminal Law when tax crimes extend to broader domains, such as causing state losses. In simpler terms, severe tax violations, such as fraud or forgery, can be considered general crimes and are subject to criminal sanctions as regulated in the Criminal Law. Additionally, there are still numerous factors hindering the prosecution of tax-related crimes, such as the complexity of tax regulations, instances of abuse of power and corruption, and the lack of taxpayer awareness to comply with applicable rules.